2017
DOI: 10.1159/000476020
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pathogenic Variant in the MITF Gene Segregating with a Unique Spectrum of Ocular Findings in an Extended Iranian Waardenburg Syndrome Kindred

Abstract: Waardenburg syndrome (WS) is a rare genetic disorder characterized by abnormal pigmentation of the hair, skin, and iris as well as sensorineural hearing loss. WS is subdivided into 4 major types (WS1-4), where WS2 is characterized by the absence of dystopia canthorum. This study was launched to investigate clinical and molecular characteristics of WS in an extended Iranian WS2 family. A comprehensive clinical investigation was performed. Peripheral blood samples were collected and genomic DNA was extracted. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
(22 reference statements)
2
7
0
Order By: Relevance
“…Consistent with previous studies [17], all three probands with STRC homozygous or compound heterozygous deletions have moderate hearing loss (PTAs of 40-50 dB HL). Fourteen of the sixteen other independent mutations identified in this study have been reported to be associated with hearing loss in previous studies, including dominant mutations EYA1 c.1276G > A (p. G426S) [18] and MITF c.877C > T (p. R293*) [19], recessive mutations PCDH15 c.4133C > T (p. T1378I) and c.1453delT (p. S485Rfs*2) [20], USH2A c.10904C > A (p.T3635 N) [21], MYO15A c.8158G > A (p. D2720N) and c.10258_10260delTTC (p.F3420-) [22], CDH23 c.7630 T > G (p. L2544 V) and c.8257G > A (p.A2753T) [20], OTOF c.2122C > T (p.R708*) and c.1194 T > A (p.D398E) [23,24], SLC26A4 c.1174A > T (p. N392Y) and c.1975G > C (p.V659 L) [25], and SMPX c.55A > G (p. N19D) [26]. One novel hemizygous mutation, c.201delT (p.E68Sfs*11) in TIMM8A, was identified in a male proband D211 as a likely pathogenic mutation since similar Based on the new genetic diagnosis, we revisited the clinical aspects of proband D289 and D554.…”
Section: Additional or Alternative Causes In Patients With Monoallelimentioning
confidence: 57%
“…Consistent with previous studies [17], all three probands with STRC homozygous or compound heterozygous deletions have moderate hearing loss (PTAs of 40-50 dB HL). Fourteen of the sixteen other independent mutations identified in this study have been reported to be associated with hearing loss in previous studies, including dominant mutations EYA1 c.1276G > A (p. G426S) [18] and MITF c.877C > T (p. R293*) [19], recessive mutations PCDH15 c.4133C > T (p. T1378I) and c.1453delT (p. S485Rfs*2) [20], USH2A c.10904C > A (p.T3635 N) [21], MYO15A c.8158G > A (p. D2720N) and c.10258_10260delTTC (p.F3420-) [22], CDH23 c.7630 T > G (p. L2544 V) and c.8257G > A (p.A2753T) [20], OTOF c.2122C > T (p.R708*) and c.1194 T > A (p.D398E) [23,24], SLC26A4 c.1174A > T (p. N392Y) and c.1975G > C (p.V659 L) [25], and SMPX c.55A > G (p. N19D) [26]. One novel hemizygous mutation, c.201delT (p.E68Sfs*11) in TIMM8A, was identified in a male proband D211 as a likely pathogenic mutation since similar Based on the new genetic diagnosis, we revisited the clinical aspects of proband D289 and D554.…”
Section: Additional or Alternative Causes In Patients With Monoallelimentioning
confidence: 57%
“…Specifically, since subunits of the SWI/SNF complex associate with the protein product of the microphthalmia transcription factor ( MITF ) gene, 6 described as a master gene for survival of melanocytes and key transcription factor regulating melanin synthesis, mutations in the SWIF genes present in CSS could affect the transcription of melanin. MITF has various isoforms 7 and mutations associated with a range of phenotypes in pigmented cells 7 . Melanocytic isoform M mutations lead to Waardenburg syndrome type 2A, an auditory pigmented syndrome with hearing loss, patchy depigmentation of the skin, and irides 7 .…”
Section: Discussionmentioning
confidence: 99%
“…MITF has various isoforms 7 and mutations associated with a range of phenotypes in pigmented cells 7 . Melanocytic isoform M mutations lead to Waardenburg syndrome type 2A, an auditory pigmented syndrome with hearing loss, patchy depigmentation of the skin, and irides 7 . In contrast, a dominant-negative mutation causes Tietze syndrome, characterized by congenital deafness and generalized albinoid-like hypopigmentation of the skin, eyes, and hair 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in PAX3 gene is mainly responsible for the clinical features of WS type I and III, whereas mutations in genes MITF, SOX10 and SNAI2 are identified in WS type II. Genetic mutations in EDN3 and EDNRB have been implicated in WS type IV [8], [6], [10], [5], [9], [19]…”
Section: Introductionmentioning
confidence: 99%